The impact of antiretroviral therapy in resource‐limited settings and current HIV therapeutics. (April 2016) - Kumarasamy, N
Abstract : Four million people of the global total of 35 million with HIV infection are from South‐East Asia. ART is currently utilized by 15 million people and has led to a dramatic decline in the mortality rate, including those in low‐ and middle‐income countries. A reduction in sexually transmitted HIV and in comorbidities including tuberculosis has also followed. Current recommendations for the initiation of antiretroviral therapy in people who are HIV+ are essentially to initiate ART irrespective of CD4 cell count and clinical stage. The frequency of HIV testing should be culturally specific and based on the HIV incidence in different key populations but phasing in viral load technology in LMIC is an urgent priority and this needs resources and capacity. With the availability of simplified potent ART regimens, persons with HIV now live longer. The recent WHO treatment guidelines recommending routine HIV testing and earlier initiation of treatment should be the stepping stone for ending the AIDS epidemic and to meet the UNAIDS mission of 90*90*90.